![(a+b)^{2}=a^{2}+2ab+b^{2} (a+b)^{2}=a^{2}+2ab+b^{2}](https://tex.z-dn.net/?f=%28a%2Bb%29%5E%7B2%7D%3Da%5E%7B2%7D%2B2ab%2Bb%5E%7B2%7D)
====================================================
![(a-b)^{2}=a^{2}-2ab+b^{2} (a-b)^{2}=a^{2}-2ab+b^{2}](https://tex.z-dn.net/?f=%28a-b%29%5E%7B2%7D%3Da%5E%7B2%7D-2ab%2Bb%5E%7B2%7D)
====================================================
![(a+b)(a-b)=a^{2}-b^{2} (a+b)(a-b)=a^{2}-b^{2}](https://tex.z-dn.net/?f=%28a%2Bb%29%28a-b%29%3Da%5E%7B2%7D-b%5E%7B2%7D)
====================================================
![(a+b)^{3}=a^{3}+3a^{2}b+3ab^{2}+b^{3} (a+b)^{3}=a^{3}+3a^{2}b+3ab^{2}+b^{3}](https://tex.z-dn.net/?f=%28a%2Bb%29%5E%7B3%7D%3Da%5E%7B3%7D%2B3a%5E%7B2%7Db%2B3ab%5E%7B2%7D%2Bb%5E%7B3%7D)
====================================================
![(a-b)^{3}=a^{3}-3a^{2}b+3ab^{2}-b^{3} (a-b)^{3}=a^{3}-3a^{2}b+3ab^{2}-b^{3}](https://tex.z-dn.net/?f=%28a-b%29%5E%7B3%7D%3Da%5E%7B3%7D-3a%5E%7B2%7Db%2B3ab%5E%7B2%7D-b%5E%7B3%7D)
====================================================
![(a+b)(a^{2}-ab+b^{2})=a^{3}+b^{3} (a+b)(a^{2}-ab+b^{2})=a^{3}+b^{3}](https://tex.z-dn.net/?f=%28a%2Bb%29%28a%5E%7B2%7D-ab%2Bb%5E%7B2%7D%29%3Da%5E%7B3%7D%2Bb%5E%7B3%7D)
====================================================
![(a-b)(a^{2}+ab+b^{2})=a^{3}-b^{3} (a-b)(a^{2}+ab+b^{2})=a^{3}-b^{3}](https://tex.z-dn.net/?f=%28a-b%29%28a%5E%7B2%7D%2Bab%2Bb%5E%7B2%7D%29%3Da%5E%7B3%7D-b%5E%7B3%7D)